Life Cycle Assessment of Amorphous Silicon Solar Cell Power Plant Using Activity-Based Approach - Chamsilpa, Muanjit; Kiatsiriroat, Tanongkiat (Journal of Renewable Energy and Smart Grid Technology, 2014)
In this study, life cycle assessment or LCA is applied to investigate environmental impacts of an amorphous silicon solar cell power plant over its entire life cycle. The first solar cell power plant of Thailand with a capacity of 500 kWp is taken as a model for the assessment. The environmental analytical results through the power plant life cycle are shown in term of environmental loads which are calculated from Numerical Environmental Total Standard or NETS method. The functional unit in this study is 1 kWh of electricity generation. The study covers the phases of solar module manufacturing, transportation from manufacturer to the power plant and electricity generation in the power plant. Activity-based approach is applied to collect the relevant data in life cycle inventory step for more accuracy results. The results show that the main environmental impact is at the manufacturing phase which offers about 98% of the total impact and the most violent problem is natural resource depletion due to raw material consumption of aluminum frame. The result which is calculated by the activity-based approach offers higher value than that of the conventional LCA due to expansion of considered boundary.